Perkembangan Masa Puber - Oti Aprillia; Nadia Gufran; Linda Yarni (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Puberty development is a significant transitional phase in an individual's life, characterized by complex physical, emotional, and psychological changes. This research aims to explain the process of puberty development from various perspectives, including the influencing factors and their impact on individuals. The research method involves synthesizing literature from various sources to provide a comprehensive picture of the changes that occurred during this time. It is hoped that the findings from this research will provide a deeper understanding of the challenges individuals face during puberty as well as their potential implications in the context of education, health and personal development.